2015
DOI: 10.1002/jrs.4690
|View full text |Cite
|
Sign up to set email alerts
|

SERS microRaman spectral probing of adsorbate-containing, liquid-overlayed nanosponge Ag aggregates assembled from fractal aggregates

Abstract: Adsorbate‐containing, nanosponge Ag aggregates overlayed by a thin (~1.5 mm) liquid layer are reported as a new type of sample for Surface‐enhanced Raman scattering (SERS) microRaman spectral measurements and adsorbate (analyte) detection. Macroscopic Ag aggregates (of about 1.5 × 1.0 × 0.025 mm size) with the nanosponge internal morphology (revealed by Scanning electron microscopy (SEM)) were prepared by 3D assembling of fused fractal aggregates (D = 1.84 ± 0.04) formed in Ag nanoparticle hydrosol/HCl/adsorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Flexible sensors capable of monitoring physiological and biomechanical signals from the human body are particularly important for life science, and can pave the way for the design of body sensor networks (BSN) for personalized healthcare [6][7][8][9]. On the other hand, surface-enhanced Raman spectroscopy (SERS), distinguished by its noninvasive, non-labeling, fingerprinttype way of sensing, and ultrahigh sensitivity, has been considered one of the most promising sensing techniques for low-dose sensing applications [10][11][12][13]. For these reasons, flexible architectures with superior SERS activity are expected to be integrated into future BSN, which will allow for real-time tracing of small changes in the human skin.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sensors capable of monitoring physiological and biomechanical signals from the human body are particularly important for life science, and can pave the way for the design of body sensor networks (BSN) for personalized healthcare [6][7][8][9]. On the other hand, surface-enhanced Raman spectroscopy (SERS), distinguished by its noninvasive, non-labeling, fingerprinttype way of sensing, and ultrahigh sensitivity, has been considered one of the most promising sensing techniques for low-dose sensing applications [10][11][12][13]. For these reasons, flexible architectures with superior SERS activity are expected to be integrated into future BSN, which will allow for real-time tracing of small changes in the human skin.…”
Section: Introductionmentioning
confidence: 99%
“…Sutrova and co‐workers studied SERS micro‐Raman spectral probing of adsorbate‐containing, liquid‐overlayed nanosponge Ag aggregates assembled from fractal aggregates. They found that the advantages of the nanosponge Ag aggregates are further demonstrated by the 40 femptomole limit of detection of 2,2′‐bipyridine (bpy) as Ag(0)‐bpy surface complex, as well as by preservation of the native structure of the cationic free‐base porphyrin, H 2 TMPyP . Yan et al .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…They found that the advantages of the nanosponge Ag aggregates are further demonstrated by the 40 femptomole limit of detection of 2,2′bipyridine (bpy) as Ag(0)-bpy surface complex, as well as by preservation of the native structure of the cationic free-base porphyrin, H 2 TMPyP. [17] Yan et al described a facile highperformance SERS substrate based on broadband near-perfect optical absorption. In this study, they prepared a broadbandvisible light absorber consisting Au nanotriangles on the surface of a continuous optically opaque gold film separated with a dielectric SiO 2 layer, which is a typical metal-insulator-metal (MIM) system, and demonstrated it as an efficient SERS substrate.…”
Section: Sers Substratesmentioning
confidence: 99%